Influence of Social Connections on Smoking Behavior across the Life Course - Thomeer, Mieke Beth (Adv Life Course Res, 2019)
Although we know much about demographic patterns of smoking, we know less about people’s explanations for when, how and why they avoid, develop, or alter smoking habits and how these explanations are linked to social connections across the life course. We analyze data from in-depth interviews with 60 adults aged 25-89 from a large southwestern U.S. city to consider how social connections shape smoking behavior across the life course. Respondents provided explanations for how and why they avoided, initiated, continued, and/or quit smoking. At various times, social connections were viewed as having both positive and negative influences on smoking behavior. Both people who never smoked and continuous smokers pointed to the importance of early life social connections in shaping decisions to smoke or not smoke, and viewed later connections (e.g., marriage, coworkers) as less important. People who quit smoking or relapsed tended to attribute their smoking behavior to social connections in adulthood rather than early life. People who changed their smoking behavior highlighted the importance of transitions as related to social connections, with more instability in social connections often discussed by relapsed smokers as a reason for instability in smoking status. A qualitative approach together with a life course perspective highlights the pivotal role of social connections in shaping trajectories of smoking behavior throughout the life course.